A inter-relação entre o ser humano e o espaço em Pedro Páramo, de Juan Rulfo - Aguiar, Larissa Walter Tavares de (2014)
This paper discusses the relationship between the setting and the characters in the novel Pedro Páramo (1955), by Juan Rulfo. In this novel, the setting complements the characters' existential profile, representing all their existential drama. Thus, the setting elements that help in the identity construction of characters in the novel gain importance. The novel does not follow a chronological order of events and there are several small stories that, in a fragmented way, create the fable. Comala, the setting where the story takes place, undergoes changes as the fable develops. In the past, the place was fertile and productive, but at the time the story begins, Comala is an almost barren region, inhabited by the ghosts of the villagers. The existing plant and animal life are related to the fate of people. The theoretical background for this research was Ecocriticism and Existentialism. These two theories discuss the philosophical implications of how humans deal with human and also non-human life in the space they live in.